Recepcja Karola Mannheima w polskiej socjologii i filozofii. Pierwsze przybliżenie = Reception of Karl Mannheim`s works in Polish sociology - Chałubiński, Mirosław (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The reception of Karl Mannheim`s works in Poland has not been widely studied yet. This paper attempts to examine that problem starting from the first comments in the years between the First and the Second World War up to the clearly determined periods after the Second World War.
Keywords: Mannheim, Karl (1893-1947); socjologia polska; filozofia